The effect of online customer shopping experience on online impulsive buying on Shopee : attitudinal loyalty as mediator and self control as moderation - Defni, Siti Salma; Sari, Astri Yuza (Marketing Management Studies, 2024)
The purpose of this study was to analyze the effect of online customer shopping experience on online impulsive buying on Shopee : attitudinal loyalty as mediator and self control as moderation. The sampling technique for this research uses purposive sampling. The sample in this study amounted to 180 respondents. Data was collected through online distribution of questionnaires and analyzed using SmartPLS software. The results of this research reveal that (1) Online Customer Shopping Experience has a positive and significant effect on Online Impulsive Buying (2) Online Customer Shopping Experience has a positive and significant effect on Attitudinal Loyalty (3) Attitudinal Loyalty has a positive and significant effect on Online Impulsive Buying (4) Online Customer Shopping Experience has a positive and significant effect on Online Impulsive Buying, mediated by Attitudinal Loyalty (5) Self-control negatively moderates the relationship between Attitudinal Loyalty and Online Impulsive Buying.